THE GEOGRAPHGIC PLACES NAMED RELATIVELY WITH “SPAR”, THEIR LOCATIONS AND CONTENTS OF THEIR TOPONYMS: Монгол орны “Жонш”-оор нэрлэсэн газар, тэдгээрийн байршил, нэрийн агуулга - Ж.Нарангарав (Acta Mongolica, 2008)
The toponyms created relatively to the natural resources of Mongolia from the “Classified Dictionary ofMongolian Toponyms” (compiled by E.Ravdan, UB, 2004, 5 volumes, 8 parts, with a CD enclosed) served a background for this research. This article deals with 72 toponyms which include the name “spar” and 20 of them are registered in the “Map of Natural Resources in the Macro-economical Zones”. These toponyms cover in general the three basic spar basins in the country. Three of the 6 mines currently functioning in Mongolia are located in the places with the names including the word “spar”.